Comparison of Multilevel Anterior Cervical Discectomy and Fusion Performed in an Inpatient Versus Outpatient Setting. Issue 8 (December 2019) - Vaishnav, Avani; Hill, Patrick; McAnany, Steven; Patel, Dil V.; Haws, Brittany E.; Khechen, Benjamin; Singh, Kern; Gang, Catherine Himo; Qureshi, Sheeraz
Study Design: Retrospective cohort study. Objective: To evaluate differences in patient factors, procedural factors, early outcomes and safety in mutlilevel anterior cervical discectomy and fusion (ACDF) in the inpatient versus outpatient setting. Methods: Patient demographics, operative factors, and outcomes of multilevel ACDF performed in an inpatient and outpatient setting were compared using Fisher's exact test for categorical and Student's t test for continuous variables. Results: Fifty-seven patients had surgery on an outpatient and 46 on an inpatient basis. Inpatients were older (56.7 vs 52.2 years, P = .012) and had a higher ASA (American Society of Anesthesiologists) class ( P = .002). Sixty percent of 2-level cases were outpatient surgeries, compared with 35% of 3-level cases ( P = .042). Outpatients had shorter operative times (71.26 vs 83.59 minutes, P < .0001) and shorter lengths of stay (8.51 vs 35.76 hours, P < .0001), lower blood loss (33.04 vs 45.87 mL, P = .003), and fewer in-hospital complications (5.3% vs 37.0%, P < .0001). Outpatients had better early outcomes in terms of 6-week Neck Disability Index (NDI) (27.97 vs 37.59, P = .014), visual analogue scale (VAS) neck (2.92 vs 4.02, P = .044), and Short Form–12 Physical Health Score (SF-12 PHS) (35.66 vs 30.79, P = .008). However, these differences did not persist at 6 months. Conclusions: The results of our study suggest that multilevel ACDF can be performed safely in the outpatient setting without an increased risk of complications compared with the inpatient setting in an appropriately selected patient. Specifically, patients' age, ASA class, and number of levels being fused should be taken into consideration. At our institution, ASA class 3, body mass index >40 kg/m 2, age >80 years, intubation time >2.5 hours, or not having a responsible adult with the patient warrant inpatient admission. Importantly, the setting of the surgery does not affect patient-reported outcomes.